40s years of shop floor resistance in a rubber factory - BHENGU, SITHEMBISO (New Agenda: South African Journal of Social and Economic Policy, 2024)
The paper reflects on 40 years (1970s to 2010s) of research on shop floor orders, resistance, and cultural formations of workers in a Durban rubber factory. The paper pieces together research on workplace in everyday life, identity, and resistance from case studies in the 1980s to the second decade of the 2000s. By revisiting theories of workplace resistance, workplace regimes and cultural formations, the paper argues that there are continuities and discontinuities in researching workplace and workers' lives throughout this 30 years continuum. Some continuities the paper explores include the persisting migrant labour and migrant identity, shop floor resistance, trade union militancy, masculinities, and trade union accountability. The paper will also show that there are discontinuities in experiences, as well as in theorising the workplace between then and now. The most significant discontinuity is the end of apartheid and its legislative and statutory measures and how they governed both the workplace and society. Webster and Von Hold (2005) call it the triple transition of economic, political, and social dimensions. For instance, the scrapping of the influx control measures and the establishment of the Labour Relations Act of 1995 constitute a significant disjuncture from the past. The paper also presents an extended approach to cultural formations approach, which critiques a bounded conception of cultural formations to beyond workplace in the 1980s literatures. The paper argues that an extended and relational approach looks at how shop floor culture is produced and reproduced in everyday life through invoking what is regarded in literature as ‘beyond workplace’ cultural formations. Migrant identities and practises have become part of what Sitas (1996) which workers invoke mostly when mobilising shop floor resistance. Similarly, ubudoda (masculinities) play out in everyday on shop floor in the ‘manufacturing of consent’ (Burawoy, 1979) and shop floor order.